Analisis Kebutuhan Pengguna untuk Perancangan Antarmuka Aplikasi Layanan Pengantaran Menggunakan User-Centered Design - Shofwatunnisa, Nida; Fathoni Mahardika; Dani Indra Junaedi; Agun Guntara (Universitas Methodist Indonesia, 2025)
Delivery services are one type of service that is widely used by the public to facilitate the process of delivering goods and orders. However, the current delivery system is still not running optimally because the use of digital technology has not been maximized. This study aims to analyze user needs in the design of a delivery service application using the User-Centered Design (UCD) method. The UCD approach was chosen because it focuses on users by placing their needs and experiences as the main aspects in the system design process. This study was conducted up to the second stage, which was to understand the context of use and identify user needs. Data collection was carried out by distributing questionnaires to ten respondents consisting of customers, business owners, and couriers. The results of the study show that users need key features such as service ordering, real-time delivery tracking, automatic notifications, and direct communication between customers and couriers. In addition, users also want an application that is easy to use, secure, and has stable performance. The results of this analysis form the basis for the application design in the next stage to produce a system that meets user needs.